1995
DOI: 10.1128/mcb.15.3.1244
|View full text |Cite
|
Sign up to set email alerts
|

Repression of Platelet-Derived Growth Factor β-Receptor Expression by Mitogenic Growth Factors and Transforming Oncogenes in Murine 3T3 Fibroblasts

Abstract: Platelet-derived growth factor BB (PDGF-BB) is an important extracellular factor for regulating the G 0 -S phase transition of murine BALB/c-3T3 fibroblasts. We have investigated the expression of the PDGF ␤ receptor (PDGF␤R) in these cells. We show that the state of growth arrest in G 0 , resulting from serum deprivation, is associated with increased expression of the PDGF␤R. When the growth-arrested fibroblasts are stimulated to reenter the cell cycle by the mitogenic action of serum or certain specific comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 58 publications
3
52
0
Order By: Relevance
“…For example we showed that PDGF␤ receptor (PDGF␤R) expression is elevated in quiescent cells and is transcriptionally down-regulated concomitantly with cell cycle re-entry (39). It appears that PDGF␤R induction during quiescence "primes" growth-arrested cells for stimulation by PDGF, and that PDGF␤R down-regulation during cell cycle entry represents a desensitization mechanism to prevent excessive or aberrant PDGFR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…For example we showed that PDGF␤ receptor (PDGF␤R) expression is elevated in quiescent cells and is transcriptionally down-regulated concomitantly with cell cycle re-entry (39). It appears that PDGF␤R induction during quiescence "primes" growth-arrested cells for stimulation by PDGF, and that PDGF␤R down-regulation during cell cycle entry represents a desensitization mechanism to prevent excessive or aberrant PDGFR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…These ®ndings provide functional evidence that the hybrid polar compounds SAHA and HMBA trigger leukemic cell death through fundamentally di erent cell cycle checkpoint-related mechanisms. In this regard, the histone deacetylase inhibitor sodium butyrate has recently been shown to induce G 1 arrest and pRb dephosphorylation in 3T3 cells lacking p21 CIP1 (Vaziri et al, 1998). Whether histone deacetylase inhibitors speci®cally exert their antiproliferative e ects through a p21 CIP1 -independent mechanism remains an unresolved issue.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the b-chain of the PDGF receptor in mouse ®broblasts was shown to be repressed by the vras or v-src oncogenes (Vaziri and Faller, 1995). The reduced number of cell surface PDGF receptors present in transformed ®broblasts may desensitize the cells to subsequent stimulation by PDGF.…”
Section: Discussionmentioning
confidence: 99%